Macrophage polarisation under immune regulation as a therapeutic target for tendon-bone healing: multifactorial regulation and mechanistic insights - Wang, Wanxue; Zhang, Liang; Jiang, Yu; Cui, Dexi; Hou, Kehao; Ren, Shengquan; Zhao, Xia; Zhang, Yingze; Yu, Ning; Qi, Chao; Xu, Kuishuai (Frontiers in Immunology, 2026)
Recovery from a variety of surgical treatments, including arthroscopic rotator cuff repair and anterior cruciate ligament restoration, depends heavily on tendon-bone healing. There is mounting evidence that the polarisation of macrophages, namely M2 polarisation, is a crucial regulating factor in the repair of tendon-bone. Early tendon-bone repair is greatly aided by M1 macrophages, which have a pro-inflammatory nature. Long-term pro-inflammatory activity, however, seriously hinders the healing process. Therefore, one of the most important challenges in tendon-bone healing is to guide macrophages into the anti-inflammatory M2 phenotype. The effect of macrophage polarisation on tendon-bone healing is thoroughly investigated in this paper, along with methods for modifying macrophage polarisation. Importantly, it demonstrates how biomaterials control this process via a variety of signalling channels, providing fresh ideas for creating cutting-edge biomaterials (such as scaffolds, hydrogels, exosomes, etc.) that encourage tendon-bone mending by focusing on immune responses from macrophages.